Diazinon and Cadmium Neurotoxicity in Rats after an Experimental Administration - Róbert Toman; Svätoslav Hluchý; Jozef Golian; Michal Cabaj; Mária Adamkovičová (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of this study was to describe the changes in cholinesterase activity in separate doses and after co-administration of cadmium and diazinon intraperitoneally and to assess toxicity and interactions of diazinon and cadmium on the nervous system in male rats. 40 male rats were randomly divided into three experimental and one control group (10 rats in each group). Blood analyzes were performed 36 hours after an intraperitoneal administration of observed compounds. The statistical evaluation of the results showed significantly (P < 0.01) reduced activity of cholinesterase in all experimental groups. The enzyme activity decreased from the control value 3.69 μkat/L to 1.81 μkat/L (diazinon group), 1.83 μkat/L (cadmium group) and 1.35 μkat/L (cadmium+diazinon group). These results indicate that both cadmium and diazinon are potent to manifest the neurotoxic effects. Moreover, a synergistic effect of the co-administered cadmium and diazinon in the nervous system has been observed.